2016
DOI: 10.1515/jtim-2016-0038
|View full text |Cite
|
Sign up to set email alerts
|

Loose ends in the eradication of Helicobacter pylori infection

Abstract: The eradication of Helicobacter pylori is essential for prevention and treatment of various conditions associated with this infection. However, its effectiveness is limited and influenced by factors linked to the bacteria and the host. In particular, influence of the biotype, smoking, diabetes mellitus, and previous treatment failure in eradication is understudied. Our center proposed to evaluate these aspects in a real life cohort by applying a questionnaire with demographic and lifestyle variables in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…In all studies included, 11 prospective studies compared the H. pylori eradication rate in diabetes and non‐diabetes 29‐39 . Eleven retrospective studies compared the proportion of diabetes and other clinic factors (age, gender, smoking, drinking, overweight, peptic ulcer disease, blood pressure, and history of NSAIDS) in groups failed and succeed in H. pylori eradication 40‐50 . Four studies further compared the level of HbA1c in diabetics failed and succeed in H. pylori eradication 30,35,37,49 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all studies included, 11 prospective studies compared the H. pylori eradication rate in diabetes and non‐diabetes 29‐39 . Eleven retrospective studies compared the proportion of diabetes and other clinic factors (age, gender, smoking, drinking, overweight, peptic ulcer disease, blood pressure, and history of NSAIDS) in groups failed and succeed in H. pylori eradication 40‐50 . Four studies further compared the level of HbA1c in diabetics failed and succeed in H. pylori eradication 30,35,37,49 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐two studies were included in these part of meta‐analysis, included 11 case‐control studies 29‐39 and 11 cohort studies 40‐50 enrolling in 5466 participants. Among them, three studies were split into two part to be included, 33,36,48 according to their group design.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, significantly successful eradication of H. pylori infection was observed in 55.0% of the overweight/obese patients and 85.4% in normal adult ( 17 ). While in a study, overweight/obese non-diabetic patients found a significantly lower rate of H. pylori eradication than control group ( 18 ). Therefore, over-weight may be independent risk factors for H. pylori eradication failure ( 17 ).…”
Section: Introductionmentioning
confidence: 94%